Physical and excess properties for binary systems containing an alcohol and ionic liquid at T = 298.15 K - E. J. González (2012)
In this paper, density, speed of sound and refractive index of six binary systems (alcohol + ionic liquid) were measured, along the whole composition range, at T = 298.15 K and atmospheric pressure. The ionic liquids used in this work are constituted by different cations (pyridinium and pyrrolidinium), anions (trifluoromethanesulfonate and dicyanamide) and alkyl-side chain (propyl- and butyl-). From the experimental data, excess molar volumes, excess molar isentropic compressions and excess refractive index were calculated and satisfactorily fitted using the Redlich-Kister equation. The obtained results show that the physical and excess properties studied in this work are dependent on the structure of the ILs, especially on the anion.